Individual Airway Closure Characterized In Vivo by Phase-Contrast CT Imaging in Injured Rabbit Lung*. Issue 9 (September 2019) - Broche, Ludovic; Pisa, Pauline; Porra, Liisa; Degrugilliers, Loïc; Bravin, Alberto; Pellegrini, Mariangela; Borges, João Batista; Perchiazzi, Gaetano; Larsson, Anders; Hedenstierna, Göran; Bayat, Sam
Abstract : Objectives: Airway closure is involved in adverse effects of mechanical ventilation under both general anesthesia and in acute respiratory distress syndrome patients. However, direct evidence and characterization of individual airway closure is lacking. Here, we studied the same individual peripheral airways in intact lungs of anesthetized and mechanically ventilated rabbits, at baseline and following lung injury, using high-resolution synchrotron phase-contrast CT. Design: Laboratory animal investigation. Setting: European synchrotron radiation facility. Subjects: Six New-Zealand White rabbits. Interventions: The animals were anesthetized, paralyzed, and mechanically ventilated in pressure-controlled mode (tidal volume, 6 mL/kg; respiratory rate, 40; FIO2, 0.6; inspiratory:expiratory, 1:2; and positive end-expiratory pressure, 3 cm H2 O) at baseline. Imaging was performed with a 47.5 × 47.5 × 47.5 μm voxel size, at positive end-expiratory pressure 12, 9, 6, 3, and 0 cm H2 O. The imaging sequence was repeated after lung injury induced by whole-lung lavage and injurious ventilation in four rabbits. Cross-sections of the same individual airways were measured. Measurements and Main Results: The airways were measured at baseline ( n = 48; radius, 1.7 to 0.21 mm) and after injury ( n = 32). Closure was observed at 0 cm H2 O in three of 48 airways (6.3%; radius, 0.35 ± 0.08 mm at positive end-expiratory pressure 12) at baseline and five of 32 (15.6%; radius, 0.28 ± 0.09 mm) airways after injury. Cross-section was significantly reduced at 3 and 0 cm H2 O, after injury, with a significant relation between the relative change in cross-section and airway radius at 12 cm H2 O in injured, but not in normal lung ( R = 0.60; p < 0.001). Conclusions: Airway collapsibility increases in the injured lung with a significant dependence on airway caliber. We identify "compliant collapse" as the main mechanism of airway closure in initially patent airways, which can occur at more than one site in individual airways. Abstract : Supplemental Digital Content is available in the text.